THE ROLE OF MONETARY POLICY IN ENSURING MACROECONOMIC STABILITY AND DEVELOPMENT - Elyor Rapikaliev (Scholar Express Journals, 2023)
The first element of monetary policy that affects inflation is aggregate demand, which depends on the price level at the national level. The transmission mechanism of monetary policy explained above mainly considers the impact on GDP through aggregate demand. In this, an approach is taken to the current state of GDP, and to the short- and medium-term periods of total demand. It should be noted that in this situation there is also a potential GDP indicator that reflects non-monetary factors. The difference between the potential and current GDP, as well as the increase in direct aggregate demand, can cause inflation at the state level. Production as a result of inflation
Keywords: Monetary policy; budget-financial goals; inflation targeting